Encyclopedia of Inorganic and Bioinorganic Chemistry 2017
DOI: 10.1002/9781119951438.eibc2499
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Metal Compounds with Protein Targets: New Tools in Medicinal Chemistry and Chemical Biology

Abstract: In cells and organisms, metal complexes can be specifically designed to interact with biomolecules and accordingly alter important biological processes. These interactions have been widely explored for targeting specific biological functions and diseases. In fact, several studies have demonstrated that inorganic chemistry offers significant diversity and versatility for the preparation of highly potent protein modulators (e.g., inhibitors). Moreover, both coordination and organometallic complexes featuring fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Development of metal compounds as potential agents capable of modifying and inhibiting Aβ aggregation is an emerging area in metal-based therapeutic drug design. A recent pioneering study by Barnham et al on Aβ aggregation inhibition by covalent binding platinum complexes triggered new research, and several Pt, Ru, Rh, and Ir complexes have been developed, principally targeting Aβ aggregation and the Cu–Aβ redox process . These complexes are able to bind Aβ covalently, interfere with the Aβ–Cu redox process, inhibit Aβ aggregation, and/or act as luminescent Aβ sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Development of metal compounds as potential agents capable of modifying and inhibiting Aβ aggregation is an emerging area in metal-based therapeutic drug design. A recent pioneering study by Barnham et al on Aβ aggregation inhibition by covalent binding platinum complexes triggered new research, and several Pt, Ru, Rh, and Ir complexes have been developed, principally targeting Aβ aggregation and the Cu–Aβ redox process . These complexes are able to bind Aβ covalently, interfere with the Aβ–Cu redox process, inhibit Aβ aggregation, and/or act as luminescent Aβ sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for new drugs, spectroscopic techniques, protein crystallography and theoretical computational methods have been applied to metallic species (SOLOMON; SCOTT; KING, 2009;SIGEL, 2014;MILLER et al, 2017), helping to understand the types of interactions carried out between metals, ligands and biomolecules, and the influence on the behavior of metallopharmaceuticals (REIS, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of cisplatin 1,2 as one of the most powerful chemotherapeutic agents against ovarian and testicular cancer, a vast library of metal complexes has been synthesized and applied in the pharmacological field, mostly as anticancer agents, but also as anti-inflammatory, antimicrobial, antirheumatic, and antimalarial drugs. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Among the non-platinum drugs, gold complexes have attracted major attention in inorganic medicinal chemistry and are gaining attention in all areas especially as anticancer agents. [18][19][20][21][22] Ever since the work of R. Koch in the 19th century, who demonstrated that K[Au(CN) 2 ] showed activity against Mycobacterium tuberculosis, a large number of gold complexes have been tested in vitro against a broad spectrum of bacteria, fungi and parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of cisplatin 1,2 as one of the most powerful chemotherapeutic agents against ovarian and testicular cancer, a vast library of metal complexes has been synthesized and applied in the pharmacological field, mostly as anticancer agents, but also as anti-inflammatory, antimicrobial, antirheumatic, and antimalarial drugs. 3–17 Among the non-platinum drugs, gold complexes have attracted major attention in inorganic medicinal chemistry and are gaining attention in all areas especially as anticancer agents. 18–22…”
Section: Introductionmentioning
confidence: 99%